Ensaios em Microeconomia Aplicada: estratégias de risco em processo licitatório e análise de política de acesso à água no ambiente escolar - Sobral, Eryka Fernanda Miranda (2020)
This thesis consists of two unrelated tests in applied microeconomics. The first one verifies the persistent behavior of fraud in drug bidding processes. Longitudinal data from companies supplying these inputs in the state of Paraíba during the period 2011-2018 and models with static and dynamic panel data were used. The results, considering the heterogeneity of the companies, validate the hypothesis that, in the environment of imperfect information with no perceived punishment, the risk strategy behavior of delivering medicines outside the validity standards is subject to temporal persistence on the one hand, and , on the other hand, that its intensity is aggravated by the degree of competition in the bidding process. The empirical analysis showed that with value at risk in previous years, they preserve about 1/3 of that incidence in the following years, which allows us to conclude that the problem of the persistence of the referred behavior seems to be more in the scope of the inspection failure and the lack of mechanism punishing the public procurement system, rather than expanding the market. In turn, the second essay assesses the effects of the Cistern on Schools Program on indicators that represent improvements in conditions that promote a healthier school environment and educational indicators of retention, dropout and school performance. For this purpose, longitudinal information from rural schools in the Brazilian semiarid region was used during the period 2007-2016. The adopted methodology consisted of two stages: (i) first, a technique for predicting propensity scores was adopted, for this purpose a model of Cox’s proportional semi-parametric duration was estimated; (ii) then, models of differences in differences were estimated, weighted by the propensity score, with control for the heterogeneity of time of exposure to treatment, in order to assess the effect of the school benefited by the cistern program in the semiarid on improvements in basic infrastructure conditions capable of promoting a healthy environment and greater welfare for students and, consequently, on school indicators. The results found show that the water access policy is capable of promoting improvements in basic infrastructure for a healthier school environment. In terms of educational indicators, there was no regular pattern in terms of the time the schools were exposed to the program, however, the calculated estimates suggest that there is, on average, a reduction in the dropout rate in primary education by about 28% and an increase in the pass rate of about 38% in schools in the Brazilian semiarid region. Such evidence supports discussions about the continuity of the program, given the existence of schools even in 2018 without access to water in the region.